Respuesta :
(₋4)²
how i got it -
1st i used the sum-product pattern
x² - 8x + 16
x² -4-4+16
then, found the common fact from the two pairs
x² - 4 - 4 + 16
(-4) - 4(-4)
rewrite in factored form
(x-4)-4(-4)
(-4) (-4)
combine to a square
(-4) (-4)
Answer:
x=4*
Step-by-step explanation:
*THIS IS ASSUMING THAT THIS EQUATION IS EQUAL TO ZERO
X^2-8x+16=0
Let's solve this equation by factoring. First, we need to find factors of 16 that add to -8. We find that those factors are -4 and -4. X^2 is simply x times x.
Therefore, when it is factored It should look like this:
(x-4)(x-4)=0
Now we take both factors and set them equal to zero:
x-4=0; x-4=0
In both of these equations we just need to add 4 to both sides.
x=4; x=4
x=4
HTH :)